Fungal oxalate decarboxylase activity contributes to Sclerotinia sclerotiorum early infection by affecting both compound appressoria development and function. (15th April 2015) - Liang, Xiaofei; Moomaw, Ellen W.; Rollins, Jeffrey A.
Summary Sclerotinia sclerotiorum pathogenesis requires the accumulation of high levels of oxalic acid (OA). To better understand the factors affecting OA accumulation, two putative oxalate decarboxylase (OxDC) genes (Ss‐odc1 and Ss‐odc2) were characterized. Ss‐odc1 transcripts exhibited significant accumulation in vegetative hyphae, apothecia, early stages of compound appressorium development and during plant colonization. Ss‐odc2 transcripts, in contrast, accumulated significantly only during mid to late stages of compound appressorium development. Neither gene was induced by low pH or exogenous OA in vegetative hyphae. A loss‐of‐function mutant for Ss‐odc1 (Δss‐odc1) showed wild‐type growth, morphogenesis and virulence, and was not characterized further. Δss‐odc2 mutants hyperaccumulated OA in vitro, were less efficient at compound appressorium differentiation and exhibited a virulence defect which could be fully bypassed by wounding the host plant prior to inoculation. All Δss‐odc2 phenotypes were restored to the wild‐type by ectopic complementation. An S. sclerotiorum strain overexpressing Ss‐odc2 exhibited strong OxDC, but no oxalate oxidase activity. Increasing inoculum nutrient levels increased compound appressorium development, but not penetration efficiency, of Δss‐odc2 mutants. Together, these results demonstrate differing roles for S. sclerotiorum OxDCs, with Odc2 playing a significant role in host infection related to compound appressorium formation and function.